2020
DOI: 10.1111/aogs.13925
|View full text |Cite
|
Sign up to set email alerts
|

Uptrend in distress and psychiatric symptomatology in pregnant women during the coronavirus disease 2019 pandemic

Abstract: Introduction: Prenatal maternal distress has a negative impact on the course of pregnancy, fetal development, offspring development, and later psychopathologies. The study aimed to determine the extent to which the coronavirus disease 2019 (COVID-19) pandemic may aggravate the prenatal distress and psychiatric symptomatology of pregnant women. Material and methods: Two cohorts of pregnant volunteer women were evaluated, one that was recruited before the COVID-19 pandemic (n = 496) through advertisements in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
356
4
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(448 citation statements)
references
References 30 publications
(53 reference statements)
24
356
4
20
Order By: Relevance
“…The present study ndings show that the prevalence of postpartum depressive and post-traumatic stress symptoms among the women experiencing childbirth during the Covid-19 pandemic was higher than that reported in previous studies before the pandemic. Literature data report that approximately 10-16% of women met major depression's criteria at 3 months postpartum [24,[33][34][35][36]. The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36].…”
Section: Discussionsupporting
confidence: 51%
“…The present study ndings show that the prevalence of postpartum depressive and post-traumatic stress symptoms among the women experiencing childbirth during the Covid-19 pandemic was higher than that reported in previous studies before the pandemic. Literature data report that approximately 10-16% of women met major depression's criteria at 3 months postpartum [24,[33][34][35][36]. The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36].…”
Section: Discussionsupporting
confidence: 51%
“…In theory, the incidence of these disorders will increase during an epidemic. One study has reported that pregnant women during covid-19 are more likely to have anxiety and depression than before (OR = 1.94, χ 2 = 10.05) (Berthelot et al 2020). However, another study showed that the incidence of depression during the outbreak did not change signi cantly compared with that before the outbreak (OR = 1, 95% CI 0.52-1.93) (Sade et al 2020).…”
mentioning
confidence: 99%
“…A recent study found that more than 1/3 of the perinatal women experienced depression during the outbreak ( 13 ), and pregnant women reported a higher rate of depression after the declaration of the COVID-19 pandemic (29.6% vs. 26.0%) ( 14 ). Besides increased depressive symptoms, perinatal women also reported elevated symptoms of anxiety, dissociation, post-traumatic stress disorder, as well as sleep disturbances during the COVID-19 pandemic ( 15 ).…”
Section: Introductionmentioning
confidence: 99%